2021
DOI: 10.1111/sms.13943
|View full text |Cite
|
Sign up to set email alerts
|

Can respiratory muscle training change the blood pressure levels in hypertension? A systematic review with meta‐analysis

Abstract: The aim was to systematically review randomized controlled trials investigating the effects of respiratory training on blood pressure control in hypertensive individuals. Systematic review with meta‐analysis was coducted following the guidelines from PRISMA statement. Searches for randomized controlled trials were performed in four electronic databases (PubMed, Cochrane Library, SCOPUS, and PEDro). Studies were included if they were randomized controlled trials that examined the impact of respiratory training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Minimally invasive decompression surgery can also be used when mechanical compression of the nerve root is the main clinicopathological manifestation. The aim of treatment is to decompress and relax the mechanically compressed nerve root and to relieve the nerve root pain [24,25]. However, minimally invasive surgery is an invasive operation, which has a variety of pain symptoms, such as surgical wound, muscle traction, and postoperative abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive decompression surgery can also be used when mechanical compression of the nerve root is the main clinicopathological manifestation. The aim of treatment is to decompress and relax the mechanically compressed nerve root and to relieve the nerve root pain [24,25]. However, minimally invasive surgery is an invasive operation, which has a variety of pain symptoms, such as surgical wound, muscle traction, and postoperative abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity is one of the treatments for patients with hypertension ( 7 ). In these meta-analyses, it could be concluded that aerobic exercise ( 32 ), isometric exercise ( 32 ), breathing-control ( 33 ), and unload respiratory muscle training ( 17 ) had the effect in reducing BP in patients with hypertension. Our meta-analysis showed that IMT, an innovative physical activity, also had an active reduction in BP which was consistent with the conclusion of the analysis showing that the antihypertensive drug was effective in SBP and DBP within 6 months (−4.2/−2.0 mmHg) ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…It ( 15 ) shows that IMT has no obvious effects on the BP of patients with hypertension, and slow breathing is more effective than IMT in lowering BP ( 16 ). Da Silva ( 17 ) has shown that loaded respiratory training can reduce BP in hypertension, however, only two RCTs were analyzed in this literature resulting in low confidence in the results. To sum up, the effects of IMT on hypertension should be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…As research has progressed, the strategies for implementing IMST have gradually diversified. Currently, they are classified mainly by maximum inspiratory pressure (MIP) into low resistance protocols (30 min/day, 30%−50% MIP) and high resistance protocols (5 min/day, 50%−75% MIP) 11 . Some regimens are combined with respiratory rate to promote the hypotensive effect of IMST by combining resistance inspiration with deep slow breathing (6, 8, 12 breaths/min) from the point of view of influencing respiratory rate.…”
Section: Introductionmentioning
confidence: 99%